Globalization of Mobile and Wireless Communications Today and in 2020 - Prasad, Ramjee; Dixit, Sudhir; Nee, Richard van; Ojanpera, Tero; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
Globalization of Mobile and Wireless Communications is a collection of cutting-edge research in mobile and wireless communications with impact on developments as far forward as 2020 and beyond. The book draws upon the insights and performed research work of leading experts in the field. Topics of discussion are related but not limited to spectrum-efficient radio interface technologies, enabling technologies for reconfigurability, wireless sensor networks, cognitive networks, coherent wireless transmission, algorithmic design, middleware for novel services and applications. The material has been edited to provide a vision for the future of mobile and wireless, towards a dynamic communication system that breaks down the barriers between communications means; and evolves and integrates business models and culture to match the technological evolution. In addition, strategies on how to overcome the technological challenges for achieving that vision are also outlined.
Preface -- Acknowledgements -- About the Editors -- Abbreviations -- 1 Introduction to Globalization of Mobile and Wireless Communications -- 2 Role of Network Operators and Manufacturers in Building a Globalized World -- Sofoklis Kyriazakos -- 3 Globalization of Mobile and Wireless Communications -- Marco Moretti -- 4 Globalisation of Wireless and Mobile Networks -- Stanley Mneney -- 5 Globalisation Of Mobile And Wireless Communications -- Peter Lindgren, et al -- 6 Access Security and Personal Privacy in Public Cellular Communication Systems -- Geir M -- Køien and Vladimir A. Oleshchuk -- 7 Security and Privacy Challenges in Globalized Wireless Communications -- Hanane Fathi -- 8 802.11n: The Global Wireless LAN Standard -- Richard van Nee -- 9 Vision on Radio Resource Management (RRM) and Quality of Service (QoS) for Wireless Communications Systems in Year 2020 -- Ljupo Jorgu?eski -- 10 On Designing Future Communication Systems -- Petar Popovski -- 11 Long-Term Development of Air Interfaces -- Ernestina Cianca -- 12 Flexible and Dynamic Use of Spectrum -- Enrico Del Re, et al -- 13 Future Perspectives for Cognitive Radio -- Marchetti and Rahman -- 14 Multi-users Participation in Bidding Process in a Congested Cellular Network -- K -- Sridhara, et al -- 15 Wavelet Radio -- Homayoun Nikookar -- 16 Cooperative Localization in a Hybrid WiMax/WiFi System -- Francescantonio Della Rosa, et al -- 17 Perspectives on Energy-Harvesting Wireless Sensor Networks -- Mary Ann Ingram, et al -- 18 Coherent Transmission -- Shinsuke Hara -- 19 Novel Services and Applications Demand Intelligent Software -- Rasmus Olsen -- 20 Let?s Assume the System is Synchronized -- Fred Harris -- Author Index -- Subject Index.
Electronic reproduction.
Keywords: Mobile communication systems; Wireless communication systems; Software radio; Artificial intelligence; Electronic book